2021
DOI: 10.1016/j.clnu.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and parenteral administration of micronutrients, phosphate and magnesium in critically ill patients: The VITA-TRACE survey

Abstract: Background & aims: Despite the presumed importance of preventing and treating micronutrient and mineral deficiencies, it is still not clear how to optimize measurement and administration in critically ill patients. In order to design future comparative trials aimed at optimizing micronutrient and mineral management, an important first step is to gain insight in the current practice of micronutrient, phosphate and magnesium monitoring and administration. Methods: Within the metabolism-endocrinology-nutrition (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
(32 reference statements)
1
21
0
4
Order By: Relevance
“…While some of the participating ICUs probably did more testing on their individually chosen D-Day, others did not change their routines. The results of a previous international survey by the MEN section regarding micronutrient practice gave similar results [19]: 120 (35.9%) respondents reported to daily measure phosphate, whereas 75 (22.5%) reported not to do routine measurements. This proportion of testing hence seems to correspond to standard practice as shown in a Danish cohort [20]: out of 190 patients admitted to their ICU, 122 (64.2%) had serum phosphate levels measured during the first 24 h of admission, of whom 25 (20.5%) were low.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…While some of the participating ICUs probably did more testing on their individually chosen D-Day, others did not change their routines. The results of a previous international survey by the MEN section regarding micronutrient practice gave similar results [19]: 120 (35.9%) respondents reported to daily measure phosphate, whereas 75 (22.5%) reported not to do routine measurements. This proportion of testing hence seems to correspond to standard practice as shown in a Danish cohort [20]: out of 190 patients admitted to their ICU, 122 (64.2%) had serum phosphate levels measured during the first 24 h of admission, of whom 25 (20.5%) were low.…”
Section: Discussionsupporting
confidence: 63%
“…Although this is evident, we insist on this point as 64.3% of centres measure Pi only 1e3 times per week. In the previously mentioned MEN survey [19], only 173 (59.2%) of the 292 respondents reporting on supplementation, regularly supplemented phosphate.…”
Section: Discussionmentioning
confidence: 94%
“…Symptoms of hypophosphatemia are non-specific, yet potentially lifethreatening, and include muscle weakness, impaired myocardial contractility and ventricular arrhythmias, respiratory failure, rhabdomyolysis, ileus, immune dysfunction, encephalopathy, and hypercalciuria [1,5]. Despite the presumed importance of maintaining normal phosphate concentration in both health and disease states, and the common presence of risk factors of hypophosphatemia, several recent surveys have indicated that routine phosphate monitoring is not widespread in patients admitted to intensive care units (ICU) and that hypophosphatemia is often not corrected [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic losses may be related to sedation administration [ 57 ] or to insufficient repletion during continuous renal replacement therapy (CRRT) [ 58 ]. Magnitude of such deficits is not well-documented in the current literature [ 59 ]. Moreover, micronutrient status is difficult to approach: routine lab assessment is not common and is expensive, and the plasma concentrations are influenced by systemic inflammatory response [ 60 , 61 ].…”
Section: Strategies To Optimize Oral Nutrition During and After Crmentioning
confidence: 99%